KARAKTER SISWA DALAM LITERASI RELIGIUS - Fadillah, Ahmad Arif; Jannati, Ahmad Rafaeli; Awaludin, Anas Farhan; Khairunnisa, Aura Zahrotun; Aini, Farasyanti Azahratul; Wardana, Ferdian Putra; Sukma, Frizori Rendy; Ningrum G., Nuryati Widya; Sabilah, Sahla; Sundari, Lilis; Utami, Ragil; Widiati, Wilda (Transpublika Publisher, 2022)
The character of children or students in religious literacy is described in this study. This research attempts to shape students' characters in order to help them become more religious and to develop their linguistic abilities. The Qualitative Method was used to acquire the data for this study. The findings of this study indicate a positive effects on the character development of students. To ensure that students' learning processes are supported, literacy implementation must be done in a supportive environment. It is well known that students' character can comprehend what has been done and what would be done after using reading literacy. The quantity of kids who are uninterested in reading is the study's main barrier.